2008
DOI: 10.1097/brs.0b013e318162340a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Etanercept, a Tumor Necrosis Factor-Alpha Inhibitor, on Neuropathic Pain in the Rat Chronic Constriction Injury Model

Abstract: This preclinical study indicates that delivering TNF-alpha inhibitors by means of a locally administered polymeric formulation provides long-lasting analgesia in an inflammatory neuropathic pain model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 69 publications
1
52
0
Order By: Relevance
“…Moreover, preemptive treatment with thalidomide prevented the development of STZ-induced thermal hyperalgesia and mechanical allodynia. Our results are in full agreement with Zanella et al (2008) and Dogrul et al (2011), who reported on improvement in thermal hyperalgesia with etanercept (TNF-α-antibodies). In contrast, recently, it has been reported that TNF-α elevates neurite outgrowth through an NF-κB-dependent pathway in cultured adult sensory neurons, and the diminished expression of TNF-α in diabetes may contribute to sensory neuropathy (Saleh et al 2011).…”
Section: Discussionsupporting
confidence: 95%
“…Moreover, preemptive treatment with thalidomide prevented the development of STZ-induced thermal hyperalgesia and mechanical allodynia. Our results are in full agreement with Zanella et al (2008) and Dogrul et al (2011), who reported on improvement in thermal hyperalgesia with etanercept (TNF-α-antibodies). In contrast, recently, it has been reported that TNF-α elevates neurite outgrowth through an NF-κB-dependent pathway in cultured adult sensory neurons, and the diminished expression of TNF-α in diabetes may contribute to sensory neuropathy (Saleh et al 2011).…”
Section: Discussionsupporting
confidence: 95%
“…Both of these cytokines were shown to produce pain hypersensitivity behaviour when administered locally to the skin or into the spinal cord [110]. TNF antibodies attenuated the development of thermal hyperalgesia and mechanical allodynia in several models of neuropathic pain [35,129,172]. Other inflammatory mediators found to induce acute pain perception in vivo in humans pointing to their potential to change ion channel function were nitric oxide (on injection) and ATP (on iontophoretic application onto skin and application onto human blister base preparations) [20,68,73].…”
Section: Processes Imitating Ion Channel Dysfunction In Inflammationmentioning
confidence: 99%
“…Recently, Zanella et al demonstrated that systemic application of etanercept reduced thermal hyperalgesia but required a 10-fold higher dose than locally administered compound in the rat constriction injury model. 53 Sommer et al reported that signifi cant decreases in thermal hyperalgesia and mechanical allodynia were seen either in local or systemic application of etanercept using chronic nerve constriction injury model. 54 These clinical and experimental fi ndings thus support the data of the present study both regarding dosage and that TNF-inhibition may reduce pain following disc rupture.…”
Section: Historical Controlsmentioning
confidence: 99%